PENGARUH PAPARAN RADIASI TERHADAP PETUGAS BRACHYTHERAPY DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK - hendrik - samosir (Saintia Fisika, 2013)
It has been done Radiation Exposure Effect Brachyterapy Officer at General Hospital Haji Adam Malik. This study aims to determine the radiation dose received by the clerk brachyterapy at General Hospital Haji Adam Malik Medan.Measurement using film radiation badges and survey meters and supporting data obtained from the Agency for Healthcare Facilities Field Supervisor. The results obtained, the dose received by the clerk brachyterapy still within the limits permitted by the Board of Trustees of Nuclear Power (BAPETEN) <5000 mrem per year, and found no effect of radiation received by the clerk. The hospital must keep monitoring radiation doses per month and require a medical examination of radiation workers.